THE EFFECT OF PHYTASE ENZYMES ADDITION ON ARTIFICIAL FEED ON HOVEN’S CARP GROWTH, Leptobarbus hoevenii (Bleeker, 1851) - Nora Sintia; Deny Sapto Chondro Utomo; Indra Gumay Yudha (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2020)
Hoven’s carp is a freshwater fish found in Indonesian. This study aims to study the effect of the addition of phytase enzymes with different doses on commercial feed on the growth rate of hoven’s carp and determine the dose of the phytase enzyme that is best for the growth of sooty fish. This research was conducted for 70 days at the Fisheries Cultivation Laboratory, Department of Fisheries and Marine Resources, Faculty of Agriculture, University of Lampung. This study used a completely randomized design with 4 treatments and 3 replications. Treatment A without the administration of phytase enzymes, B giving phytase enzymes 250 mg/kg of feed, C giving phytase enzymes 500 mg/kg feed, D giving phytase enzymes 750 mg/kg of feed. The parameters observed were absolute length growth, absolute weight growth, daily growth rate, SR, FCR, and protein retention. The results showed that the administration of phytase enzymes had an effect on fish growth with a dose of phytase enzyme 750 mg/kg of feed showing good results.